Spectroscopic studies of physical properties of crystalline silicon nanoparticle systems - Falcão, Bruno Teixeira de Poças (2020)
Crystalline silicon nanoparticles (Si-NPs) are a promising environmentally friendly nanomaterial for (opto)electronic and biomedical applications, owing to their unparalleled and size-tuneable physical and chemical properties. The controlled adaptation of Si-NPs for specific applications and the effective materialization of nanosilicon-based technologies can only be achieved through a deep characterization and a fundamental understanding of the properties of Si-NPs, including unveiling the phenomena ruling these materials at the nanoscale. This thesis focuses on the study of physical properties of Si-NPs synthesized in nonthermal plasmas, with sizes in the nanometre range and with different forms of surface termination. These materials are investigated theoretically and experimentally, with emphasis on spectroscopic studies, in view of understanding electron-phonon interactions under illumination, of linking the evolution of the oxidation phenomena with the appearance and the nature of strain, and of solving various open questions related to the recombination of charge carriers and origin of light emission. Through several Raman experiments conducted on surface-oxidized Si-NP thin films and, comparatively, on bulk crystalline silicon (c-Si), it is found that under moderate/high optical excitation the low electrical transport and reduced thermal conductivity of the Si-NPs leads to a nonthermal population of optical phonons. In general, this phenomenon may invalidate a reliable estimation of the temperature of nanomaterials from Raman spectroscopy. The phonon confinement model (PCM) is improved by considering the effects of anisotropy and splitting of the optical phonon dispersion curves, through which it is demonstrated the importance of these effects in the accurate estimation of the Si-NPs size based on the size-dependent shift and broadening of the Raman spectrum. The evolution of the natural surface oxidation process of H-terminated Si-NPs is monitored by Raman spectroscopy and infrared measurements as a function of air exposure time. The obtained experimental variations of the Raman shift and linewidth are compared with theoretical predictions from the PCM, from which it is concluded that in H-terminated Si-NPs the strain is negligible and that the continuous growth of an oxide shell leads to the appearance of an increasing compressive stress (up to 1.2 GPa). Based on several photoluminescence studies, it is found that, for Si-NPs with average size of ~ 3 nm, the origin of the luminescence changes from involving solely core-related states to core- plus surface-related states upon development of a surface oxide. In addition, it is shown that, for surface-oxidized Si-NPs, the relative importance of these two radiative recombination channels has a clear dependence on the nanoparticle size. For Si-NPs with sizes larger than ~ 3.2 nm, the luminescence is dominated by optical transitions originating within the nanoparticle core, whereas for sizes smaller than ~ 2.8 nm the luminescence becomes quickly dominated by transitions involving the oxide shell as the size decreases. Moreover, it is established that, independently of the surface passivation, the (non)radiative recombination of photo-generated charge-carriers is dominated by monomolecular processes involving defect-induced states at relatively low excitation powers and by bimolecular processes involving sub-band gap states at high excitation powers. Further, it is found that H-terminated Si-NPs are quite sensitive to photo-excitation even under residual oxygen and water molecule exposure due to surface oxidation catalysed by illumination, which should have a significant impact on inter-NP connectivity and in physical properties like thermal and electrical conductivities. This work highlights the importance of spectroscopy techniques in the investigation of the physical properties of Si-NPs.